Discourse markers in early Koine Greek: cognitive-functional analysis and LXX translation technique - Fresch, Christopher J. (Septuagint and Cognate Studies, 2023)
Cover -- Contents -- Acknowledgments -- Abbreviations -- 1. Introduction -- 2. δέ -- 3. εἰ μή and ἐὰν μή -- 4. ἀλλά -- 5. ἀλλ᾽ ἤ -- 6. μέν -- 7. Conclusion -- Bibliography -- Index of Ancient Sources -- Index of Modern Authors.